2007
DOI: 10.18388/abp.2007_3239
|View full text |Cite
|
Sign up to set email alerts
|

The role of actin and microtubule networks in plasmid DNA intracellular trafficking.

Abstract: This work is focused on the function of the microtubule and actin networks in plasmid DNA transport during liposomal transfection. We observed strong binding of plasmid DNA-lipid complexes (lipoplexes) to both networks and directional long-range motion of these lipoplexes along the microtubules. Disruption of either of these networks led to the cessation of plasmid transport to the nucleus, a decreased mobility of plasmids, and accumulation of plasmid DNA in large aggregates at the cell periphery. Our findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 17 publications
6
23
0
Order By: Relevance
“…Despite this, however, a clear-cut mechanism-based explanation of LFN superior performances is still missing. In this regard, available data support a role of microtubules in the active, vesicle-mediated, transport of LFN/DNA complexes towards the nucleus, analogously to what happens for some viruses 7 . This is somewhat surprising, however, in light of the clear correlation between active transport along microtubules and final localization of the DNA payload within acidic/digestive lysosomal compartments, as demonstrated for a number of alternative lipid-based formulations 9 10 .…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Despite this, however, a clear-cut mechanism-based explanation of LFN superior performances is still missing. In this regard, available data support a role of microtubules in the active, vesicle-mediated, transport of LFN/DNA complexes towards the nucleus, analogously to what happens for some viruses 7 . This is somewhat surprising, however, in light of the clear correlation between active transport along microtubules and final localization of the DNA payload within acidic/digestive lysosomal compartments, as demonstrated for a number of alternative lipid-based formulations 9 10 .…”
supporting
confidence: 57%
“…As mentioned earlier, contrary views exist on this point. In more detail, Ondřej and colleagues showed that LFN/DNA complexes displayed directional motion toward the cell nucleus 7 . They observed strong binding of DNA-lipid complexes to the cytoskeleton and directional long-range motion of these lipoplexes along the microtubules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only was the shape of the nuclei changed, but also the size and the number of nuclear actin aggregates decreased by more than 50% (not shown). Non-irradiated but latrunculin B-treated cells showed a significantly higher number of DSBs per nucleus than did cells not treated with the actin polymerization inhibitor , and plasmids localized inside the nucleus (arrows 6-7) (see also Ondrej et al, 2007). (B) Image of a fibroblast after inhibition of actin polymerization using latrunculin B.…”
Section: Dsbs As a Destination For Plasmid Dnamentioning
confidence: 99%
“…Although genomic DNA is locally constrained, showing only very limited diffusion in interphase nuclei of living cells (Chubb et al, 2002), little is known about the dynamics and localization of small circular DNA molecules that invade cells as a result of virus infection, during gene therapy, or during experimental cell transfection (Molas et al, 2003). When a foreign DNA was introduced into a cell by transfection, it must cross the plasma membrane, move through the cytoplasm using actin and microtubule networks (Ondrej et al, 2007), enter the nucleus, and then locate to a specific site appropriate for its integration and expression. Once foreign DNA has arrived at the nuclear envelope, it must either wait until the cell divides or be specifically imported through the nuclear pore complex to the nucleoplasm as was performed using exogenous DNA binding with NLS (nuclear localization se-quences) containing peptide (Munkonge et al, 2003).…”
Section: Introductionmentioning
confidence: 99%